The Development of Miniature Dress Form from Spunbound Material as Three-Dimensional Presentation Media in Vocational Education - Trisnani Widowati; Anik Maghfiroh; Clarita Apriliani (Jurnal Penelitian Pendidikan, 2025)
Vocational education involves many practical activities requiring direct examples or authentic media for effective learning. In fashion vocational education, three-dimensional media has emerged as the predominant choice for instructional presentation. This research aimed to develop products and systematically analyze the quality, composition, and effectiveness of miniature dress forms fabricated from spunbound as three-dimensional presentation media. The present study employed a research and development method that utilized the ADDIE model and a quantitative descriptive approach. The study involved 66 participants, including six expert validators, 20 small-scale, and 40 large-scale tests. The results obtained demonstrated that the miniature dress form, fabricated from spunbond material, exhibited quality (96.72), composition (97.03), and effectiveness (96.56) metrics that collectively fall within the high category, thus substantiating its efficacy as a three-dimensional presentation medium for fashion vocational education. It is therefore anticipated that the miniature dress form made from spunbond will be utilized as a three-dimensional presentation medium within the context of fashion vocational education.